Cervical Lymphangiomas in Children: Non-Surgical Treatment with Focus on Sclerotherapy. Literature Review (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: cervical lymphangiomas; surgery; sclerotherapy; sclerosing agents